Crimes against the Rohingya in Myanmar and Mechanisms to Address them from the Perspective of the International Criminal Court - Gghabouli, Mona; Boussadia, Raouf (Journal of Legal Studies and Researches, 2020)
This article aims to illustrate how the investigative mechanism available to the International Criminal Court to stop impunity for crimes committed and still committed by Myanmar state forces against the Rohingya Muslim minority is enforced. We have concluded that the actions of these forces are international crimes that are consistent in the court system, and therefore the jurisdiction of the latter extends to punish them despite the fact that Myanmar is a non-party state, for several reasons in order to achieve international criminal justice.